2010
DOI: 10.1186/1471-2415-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Refractive ocular conditions and reasons for spectacles renewal in a resource-limited economy

Abstract: BackgroundAlthough a leading cause of visual impairment and a treatable cause of blindness globally, the pattern of refractive errors in many populations is unknown. This study determined the pattern of refractive ocular conditions, reasons for spectacles renewal and the effect of correction on refractive errors in a resource-limited community.MethodsA retrospective review of case records of 1,413 consecutive patients seen in a private optometry practice, Nigeria between January 2006 and July 2007.ResultsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…This is in agreement with previous report by Iakho and Mohamed Ali [19]. A female preponderance for presbyopia was observed in studies by Patel and West [29][30][31][32][33], Ayanniyi et al [13,14] and Adenuga and Samuel [4].…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with previous report by Iakho and Mohamed Ali [19]. A female preponderance for presbyopia was observed in studies by Patel and West [29][30][31][32][33], Ayanniyi et al [13,14] and Adenuga and Samuel [4].…”
Section: Discussionsupporting
confidence: 82%
“…[18] A study in southwestern Nigeria showed that presbyopia accounted for 35.3% of patients with refractive error and one-and-half times commoner in females than in males. [22] Our study showed that most presbyopic patients require correction for distance and hence the need to refract all patients with presbyopia, rather than offer subjective near correction alone. Other studies did not report a similar trend.…”
Section: Discussionmentioning
confidence: 95%
“…This estimated output was calculated based on the finding in the literature that 90 per cent of refractions in most developing countries are in the presbyopic populations …”
Section: Methodsmentioning
confidence: 99%